Strategic management of digital transformation in aqidah akhlak learning at islamic senior high schools - Ahmad Najih Musoffa Fuadi; Arim Irsyadulloh Albin Jaya; Dyah Ayu Fitriana; Ibrahim bin Salem (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Technological developments encourage Islamic educational institutions to adopt digital learning models that remain grounded in Islamic values. This study examines the strategic digital transformation in the management of Aqidah Akhlak learning at Madrasah Aliyah Sunniyyah Selo. The research problem arises from the gap between the growing discourse of digital learning and its limited managerial implementation in Islamic educational institutions. Guided by organizational change theory and Islamic educational management principles, the study seeks to answer how digital transformation can be strategically formulated, implemented, and evaluated within the context of Aqidah Akhlak learning. Using a qualitative field research approach, data were collected through interviews, observations, and document analysis involving teachers, principals, and digital teams. The validity of the findings was tested through source triangulation. The findings reveal that the transformation process follows three key stages formulation, implementation, and evaluation supported by stakeholder collaboration and continuous improvement cycles. This digital transformation also shifted classroom interaction, positioning teachers as facilitators and students as active participants. The study reveals that effective digital transformation requires managerial alignment between leadership vision, teacher competence, and technological infrastructure. Theoretically, the study contributes to the literature on Islamic value-based digital learning by integrating managerial and pedagogical dimensions. Practically, it provides actionable insights for teachers, principals, and policymakers at the Ministry of Religious Affairs (Kemenag) on how to manage digital transformation effectively while preserving Islamic values. This research underscores that successful digitalization in Islamic education requires not only technological readiness but also moral, spiritual, and strategic alignment across institutional levels.